Compensatory treatment of Angle Class III malocclusion with anterior open bite and mandibular asymmetry - Sobral,Marcio Costa (2012)
Class III malocclusion is characterized by anterior posterior dental disharmony, either with or without skeletal discrepancies. Facial esthetics may be compromised to a greater or lesser degree, depending on the magnitude of the discrepancy, and is one of the main factors motivating individuals to seek orthodontic treatment. In adult patients, therapy may be performed by means of dental compensation, in simpler cases, or in more severe situations, by means of association between Orthodontics and Orthognathic Surgery. The present article is a clinical case report of a patient with a vertical facial pattern, Angle Class III malocclusion, with open bite and important facial asymmetry. The patient was treated in a compensatory manner with extractions, using extra-oral appliances on the mandibular arch with high pull, applying the principles of the Tweed-Merrifield technique. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO) as part of the requisites for becoming a BBO Diplomate.